Parents' view on the National Assessment of Knowledge at the end of the second period - Mateja Škalič; Milena Ivanuš Grmek (University of Maribor Press, 2017)
The article presents parents' views on the National Assessment of Knowledge at the end of the second educational period. In more detail we present the views of parents on the necessity of the National Assessment of Knowledge and on encouraging children to prepare for it. In the theoretical part we define assessments and further present The National Assessment of Knowledge. We then proceed to present the results of a survey conducted in 2014. The study involved 209 parents of pupils in the 6th grade from the Podravje and Pomurje region. The survey results show that the child's accomplishment at the National Assessment of Knowledge provides good feedback for the parents regarding the child's knowledge, however, they also believe it does not show a comprehensive overview of knowledge. Parents who have completed primary school and parents, who live in the Pomurje region, attribute a more prominent role in encouraging children to prepare for The National Assessment of Knowledge to the teachers, rather than themselves. The survey results alert us to the fact that children from the Pomurje region are in a less stimulating environment in terms of parents' involvement.